The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1158/1541-7786.mcr-10-0474
|View full text |Cite
|
Sign up to set email alerts
|

Forced Activation of β-Catenin Signaling Supports the Transformation of hTERT-Immortalized Human Fetal Hepatocytes

Abstract: Hepatocarcinogenesis is a multistep process driving the progressive transformation of normal liver cells into highly malignant derivatives. Unlimited proliferation and telomere maintenance have been recognized as prerequisites for the development of liver cancer. Moreover, recent studies identified illegitimate b-catenin signaling as relevant hit in a considerable subset of patients. To further investigate the currently not wellunderstood malignant evolution driven by telomerase and b-catenin, we monitored cyt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…In this model, telomerase inhibition showed that short-term expansion of transformed clones was not telomerase dependent (Wege et al 2011).…”
Section: R133 Review a Pestana And Others Tert Biology And Function Imentioning
confidence: 88%
See 1 more Smart Citation
“…In this model, telomerase inhibition showed that short-term expansion of transformed clones was not telomerase dependent (Wege et al 2011).…”
Section: R133 Review a Pestana And Others Tert Biology And Function Imentioning
confidence: 88%
“…Another study described that illegitimate activation of B-Catenin signalling enhances the transformation from immortalisation to malignant growth in human foetal hepatocytes (Wege et al 2011). In this model, telomerase inhibition showed that short-term expansion of transformed clones was not telomerase dependent (Wege et al 2011).…”
Section: R133 Review a Pestana And Others Tert Biology And Function Imentioning
confidence: 92%
“…Indeed, recent observations that constitutive expression of β-catenin increases cell cycle progression, and promotes full malignant transformation in TERT-immortalized human fetal hepatocytes, with up-regulation of genes mediating invasion and angiogenesis [49], attest to the significance of non-canonical telomerase activities during initiation and progression of cancer. In our study we observed that esophageal cancer cells expressing A279T had short telomeres relative to cells constitutively expressing wtTERT; these findings are consistent with observations by Vulliamy et al [22] that leukocytes from individuals with A279T genotype have short telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…This resembles the transcriptional program regulated by Wnt, a well known player in stem cell maintenance, cellular transformation and proliferation [51][52][53][54][55]. TERT acts as a transcription factor in β-catenin complexes.…”
Section: Regulation Of Gene Expression By Telomerasementioning
confidence: 96%